IMPORTANCE OF STAFF APPEARANCE ON CUSTOMER SATISFACTION AND LOYALTY IN UZBEK RESTAURANTS (Scientific Journal of Actuarial Finance and Accounting, 2024)
This study investigates the influence of staff appearance on customer satisfaction and loyalty in Uzbek restaurants. Using a mixed-method approach, including surveys and field observations, the research explores how the physical appearance of staff impacts customer perceptions and their subsequent loyalty. The findings suggest that well-groomed and professionally dressed staff are perceived as more competent and hospitable, which significantly enhances customer satisfaction and encourages repeat business.